Book Review - Poškaitė, Loreta (Acta Orientalia Vilnensia, 2011)
Vilnius University, Centre of Oriental StudiesArthur Kleinman, Yunxiang Yan, Jing Jun, Sing Lee, Everett Zhang, Pan Tianshu, Wu Fei, Guo Jinhua.Deep China. The Moral Life of the Person, What Anthropology and Psychiatry Tell Us about China Today, Berkeley, Los Angeles, London: University of California Press, 2011, pp. 322. ISBN 978-0-520-26945-3 (paperback), $29.95, £19.95